Family Meetings : How to Build a Stronger Family and a Stronger Business - Aronoff, Craig E and Ward, John L. (Basingstoke Palgrave Macmillan, 2011)
Regular meetings help build a strong family. And a strong family has a much better chance at long term success. In Family Meetings, authors Aronoff and Ward show that holding regular meetings is one of most important ways of ensuring less conflict and more collaboration.
Include Index
Keywords: Family corporations--Management